2023
DOI: 10.3390/cancers15112952
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Cabozantinib in Patients Previously Treated with Atezolizumab/Bevacizumab for Advanced Hepatocellular Carcinoma—Importance of Good Liver Function and Good Performance Status

Abstract: (1) Background: This study aimed to investigate clinical outcomes for cabozantinib in clinical practice in patients with advanced hepatocellular carcinoma (HCC) previously treated with atezolizumab plus bevacizumab (Atz/Bev), with a focus on whether patients met criteria of Child–Pugh Class A and Eastern Cooperative Oncology Group performance status (ECOG-PS) score 0/1 at baseline. (2) Methods: Eleven patients (57.9%) met the criteria of both Child–Pugh class A and ECOG-PS score 0/1 (CP-A+PS-0/1 group) and eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In our cohort, nivolumab showed a longer OS compared to sorafenib only despite the presence of multiple negative confounders, such as the presence of more co-morbidities, more patients with ECOG 2 status, BCLC C status, extravascular invasion, and CTP B status in the nivolumab arm. In previous analyses of patients with uHCC, CTP score, BCLC stage and performance status have been prognostically valuable to predict OS [20][21][22][23]. The survival of sorafenib-treated CTP B patients in our study (5 months) was comparable to real-life data reported from the GIDEON registry (5.2 months) [20].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In our cohort, nivolumab showed a longer OS compared to sorafenib only despite the presence of multiple negative confounders, such as the presence of more co-morbidities, more patients with ECOG 2 status, BCLC C status, extravascular invasion, and CTP B status in the nivolumab arm. In previous analyses of patients with uHCC, CTP score, BCLC stage and performance status have been prognostically valuable to predict OS [20][21][22][23]. The survival of sorafenib-treated CTP B patients in our study (5 months) was comparable to real-life data reported from the GIDEON registry (5.2 months) [20].…”
Section: Discussionsupporting
confidence: 76%
“…The relevance of maintained hepatic reserve appears crucial in prolonging survival in uHCC [21,22,25].…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, nivolumab showed a longer OS compared to sorafenib, despite the presence of multiple negative confounders, such as the presence of more co-morbidities, more patients with ECOG 2 status, BCLC C status, extravascular invasion, and CTP B status in the nivolumab arm. In previous analyses of patients with uHCC, the CTP score, BCLC stage, and performance status have been prognostically valuable in predicting OS [ 20 , 21 , 22 , 23 ]. The survival of sorafenib-treated CTP B patients in our study (5 months) was comparable to real-life data reported from the GIDEON registry (5.2 months) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, by adequately monitoring patients and matching the dose of lenvatinib, AEs could be safely managed, and the results suggest that this enables even advanced HCC patients with symptoms of anorexia or fatigue to experience a normal level of benefits from lenvatinib treatment. The desired effects of ICIs (e.g., atezolizumab or bevacizumab) on the immune system tend to be long-lasting, and, after treatment of HCC patients with ICIs, favorable effects have been reported for the use of the anti-VEGFR-2 monoclonal antibody ramucirumab or the multi-kinase inhibitor cabozantinib (an MTA) as second-line therapies (34)(35)(36). Our results are in line with these findings, and support the possibility of a favorable pseudo-combination therapy effect when administering agents that inhibit other cellular signaling pathways to patients who earlier received immunotherapy (37).…”
Section: Discussionmentioning
confidence: 99%